Direct Determination of the Steady State and Time‐Resolved Quasi‐Fermi Level Separation in Organic Solar Cells from Electroluminescence Measurements. Issue 20 (26th July 2022) - Faisst, Jared; List, Mathias; Heinz, Friedemann; Würfel, Uli
Abstract: The detection of photoluminescence (PL) is an important characterization method for many photovoltaic technologies providing direct information about the separation of the quasi‐Fermi levels (QFL), Δ E F . However, for organic solar cells, the PL is dominated by excitons, which decay radiatively before they form free charge carriers via dissociation at donor/acceptor interfaces. This (major) part of the PL signal does therefore not correlate with Δ E F . In contrast, electroluminescence (EL) stems from injected electrons and holes, which recombine via charge transfer (CT) states. This work evaluates whether Δ E F can be derived directly from EL emission and whether this also holds true for transient measurements. To do so, Δ E F data derived from steady‐state EL measurements of highly efficient organic solar cells are compared with the electrical voltage, both in the dark and under illumination at equal recombination currents. Furthermore, Δ E F is also, to the best of the authors' knowledge for the first time, derived from transient EL experiments, and in all cases, an excellent agreement is found. This means that the occupation of CT states is in equilibrium with the free charge carrier densities and can, thus, be described by the same QFL, even in the transient case. Abstract : The quasi‐Fermi level separation inside the absorber layer of different organic solar cells (D18:Y6, PV‐X plus, and P3HT:PC60BM) is derived from steady‐state electroluminescence. Without significant surface recombination, this quantity equals the electrical voltage between the terminals of the device. In addition, it is shown for the first time that this correlation also holds in the transient case.